From molecule to men: molecular basis of congenital cardiovascular disorders - Zehender, Manfred Karl-Heinz; Just, Hanjörg; Breithardt, Günter (Steinkopff Imprint: Steinkopff, 2000)
From molecule to man: Medical research has indeed taken this direction, and major improvements of our understanding of the pathophysiology and epidemiology of disease have been achieved. The molecular basis of the congenital cardiovascular disorders has been extended from relatively few congenital malformations into everyday illnesses such as diabetes mellitus, hyperlipoproteinaemea, and arterial hypertension. The monogenic and, more difficult, polygenic basis for a vast majority of cardiovascular disorders are being defined more precisely from year to year. This book gives an overview of what has been achieved so far and defines the current position